5-Aminoimidazole-4-carboxamide-1-β-4-ribofuranoside (AICAR) enhances the efficacy of rapamycin in human cancer cells - Mukhopadhyay, Suman (Cell Cycle, 2015)
mTOR – the mammalian/mechanistic target of rapamycin – has been implicated as a key signaling node for promoting survival of cancer cells. However, clinical trials that have targeted mTOR with rapamycin or rapamycin analogs have had minimal impact. In spite of the high specificity of rapamycin for mTOR, the doses needed to suppress key mTOR substrates have proved toxic. We report here that rapamycin when combined with AICAR – a compound that activates AMP-activated protein kinase makes rapamycin cytotoxic rather than cytostatic at doses that are tolerated clinically. AICAR by itself is able to suppress mTOR complex 1 (mTORC1), but also stimulates a feedback activation of mTORC2, which activates the survival kinase Akt. However, AICAR also suppresses production of phosphatidic acid (PA), which interacts with mTOR in a manner that is competitive with rapamycin. The reduced level of PA sensitizes mTORC2 to rapamycin at tolerable nano-molar doses leading reduced Akt phosphorylation and apoptosis. This study reveals how the use of AICAR enhances the efficacy of rapamycin such that rapamycin at low nano-molar doses can suppress mTORC2 and induce apoptosis in human cancer cells at doses that are clinically tolerable.